Bilateral Technique of Penis Flap with Scrotum Skin in Penile Paraffinoma Cases: A Case Report - Venerabilis Estin Namin; Herbert Soritua Silalahi; Imam Hafidh Zaini (HM Publisher, 2023)
Background: Paraffin injection into the penis is one way that people see it as increasing penis size. But many do not know that paraffin injection actually causes side effects in the form of penile paraffinoma. This study aimed to describe the management of paraffinoma using bilateral techniques. Case presentation: A 40-year-old married man came to the emergency room at Samuel J. Moeda Naval Hospital, Kupang, with complaints of pain and swelling of the penis for 6 hours. The pain felt to get worse when the penis was erected. The genital organs found swelling of the entire penile skin accompanied by tenderness and induration. The bilateral scrotal flap technique was because the scrotal skin had many blood vessels, good flexibility, little adipose tissue, thin skin, and could feel erogenous sensations almost the same as the physiological characteristics of the penile skin. Conclusion: Bilateral scrotal flap technique on the penile shaft is a surgical technique that is quite effective in eradicating paraffin from penile tissue.